Learning from usability testing of an arts‐based knowledge translation tool for parents of a child with asthma - Mandy M. Archibald; Shannon D. Scott (Wiley, 2019)
Abstract Aim Digital, art‐ and story‐based resources can be viable and engaging knowledge translation strategies in health care. Understanding the usability of these approaches can help maximize their impact. The aim of this work is to understand what aspects of 'My Asthma Diary', an art‐based digital knowledge translation tool for parents of children with asthma, has an impact on usability. Design Sequential explanatory mixed methods pilot study. Methods Eighteen parents of children with asthma reviewed 'My Asthma Diary' in a paediatric emergency department and completed a usability questionnaire. Follow‐up interviews were conducted with five parents and analysed with qualitative description. Results We identified four themes which complemented the quantitative results: (a) the eBooks are relatable and mirror personal experience; (b) the digital format is convenient and easy to navigate; (c) the narrative structure aids learning; and (d) the narrative and illustrations are synergistic. We summarize core usability considerations for subsequent research and creative knowledge translation tool development in other contexts.